Evaluation of Active aging condition in the elderly in Tehran and its relative factors - kashanimovahhed, Bahareh; Bahrami, Alireza; Bodaghabadi, Mohammad; Shokri, Masoumeh (Researcher Bulletin of Medical Sciences, 2020)
Scientific and international assemblies now consider active aging as an important concept in an aging positive approach. The goal of this study is to evaluate active aging condition in the elderly in Tehran and its relative factors. This study is a cross-sectional descriptive research, which is performed in June and July 2018. The sample includes 131 old adults (people with the age of 60 or more than 60) living in Shemiranat area of Tehran. These people are selected via two-stage cluster sampling. Data- gathering tool includes “active aging” questionnaire, “life satisfaction in elderly” questionnaire and demographic data of old adults. Data analysis is performed by SPSS software and also using descriptive statistics, t-test and Pearson correlation. In this study, data suggest that only 9.2 % of case study were at the higher level of aging. According to six index of active aging, most respondent status were weak in “active mind maintenance” and “social-institutional participation” and were average in “agent attitude”, “physical-functional activity”, “social contacts” and “productive engagement”. There were reverse and meaningful relation between age and number of children variables and active aging ( and there were positive and meaningful relation between education, occupation and income level variables ( . However, there were no meaningful relation between sex and marital status . The results of this study also suggest that there is positive and meaningful relation between “life satisfaction of elderly” and “active aging” ( . According to low level of active aging in old adult of Tehran, this issue needs to be addressed by the authorities. Therefore, it is necessary to consider and modify the needed solutions to improve the level of active aging and special services for this group in the future planning of the country. On the other hand, considering the concept of active aging has recently been raised in the scientific community, researchers need to plan and implement more extensive studied in this area.